Dysregulated repair in asthmatic paediatric airway epithelial cells: The role of plasminogen activator inhibitor-1 - Stevens, P.T.; Kicic, Anthony; Sutanto, E.N.; Knight, D.A.; Stick, S.M. (WILEY-BLACKWELL, 2008)
Background: Asthma is associated with structural changes to airways such as extracellular matrix deposition and epithelial damage. Evidence suggests that asthmatic airway epithelial repair is abnormal and that elevated plasminogen activator inhibitor-1 levels observed in asthma may be involved in the epithelial repair process and in excessive matrix accumulation. Objective: To assess the ability of asthmatic airway epithelial cells (AECs) to repair mechanically induced wounds and to investigate the role that plasminogen activator inhibitor-1 plays in the repair process. Methods: AECs were isolated from atopic asthmatic and healthy non-atopic children by bronchial brushing, subcultured and wound repair experiments were performed. Plasminogen activator inhibitor-1 gene expression was assessed using real-time PCR while protein activity was measured in cell lysates as well as plasma. The role of plasminogen activator inhibitor-1 in epithelial proliferation and wound repair was investigated using siRNA. Results: Cells from asthmatic children have a significantly longer repair time in comparison with cells from otherwise healthy donors. Plasminogen activator inhibitor-1 mRNA expression was up-regulated 68-fold in freshly isolated asthmatic cells compared with normal cells, and protein levels were also significantly elevated in the asthmatic cell lysates, but plasma levels were similar in both groups. Plasminogen activator inhibitor-1 cells expression increased in both cohorts during culture. Gene silencing substantially reduced the rate of proliferation in asthmatic and healthy cells. Mechanical wounding of epithelial monolayers induced plasminogen activator inhibitor-1 expression in asthmatic and non-asthmatic cohorts, while gene silencing delayed wound repair of healthy cell, with minimal effect on those from asthmatics. Conclusion: Asthmatic AECs are inherently dysfunctional in their ability to repair wounds; plasminogen activator inhibitor-1 mRNA and protein activity are constitutively up-regulated in asthmatic epithelium and play functional roles in both proliferation and repair of healthy cells. In asthmatic cells, elevated plasminogen activator inhibitors-1 levels fail to stimulate epithelial repair. © 2008 The Authors.